2014
DOI: 10.1016/j.jbiomech.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of femoral graft placement on cartilage thickness after anterior cruciate ligament reconstruction

Abstract: Altered joint motion has been thought to be a contributing factor in the long-term development of osteoarthritis after ACL reconstruction. While many studies have quantified knee kinematics after ACL injury and reconstruction, there is limited in vivo data characterizing the effects of altered knee motion on cartilage thickness distributions. Thus, the objective of this study was to compare cartilage thickness distributions in two groups of patients with ACL reconstruction: one group in which subjects received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 53 publications
(92 reference statements)
1
51
0
Order By: Relevance
“…Subjects were asked to not perform any strenuous lower body activity the night prior to or the morning of their participation. Subjects first lay supine on a stretcher immediately outside of the MR suite for 45 minutes to minimize cartilage deformation prior to scanning 6, 33, 39 . Subjects were then moved to a wheelchair without any weightbearing and transported to the MR suite where they underwent pre-activity imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were asked to not perform any strenuous lower body activity the night prior to or the morning of their participation. Subjects first lay supine on a stretcher immediately outside of the MR suite for 45 minutes to minimize cartilage deformation prior to scanning 6, 33, 39 . Subjects were then moved to a wheelchair without any weightbearing and transported to the MR suite where they underwent pre-activity imaging.…”
Section: Methodsmentioning
confidence: 99%
“…These calculations were used to generate cartilage thickness maps for each knee (Figure 2). The femoral and tibial bony surfaces of the pre-activity and post-activity models were aligned using an iterative closest point technique 11, 33, 48 . This registration process enabled the site-specific measurement of cartilage strain using the pre-activity and post-activity models.…”
Section: Methodsmentioning
confidence: 99%
“…As already stated, given the better understanding of ACL anatomy, there has been a transition from the so-called isometric reconstruction to anatomic reconstruction of the ACL [4,5]. Allegedly, some studies pointed out that anatomical tunnel placement results in superior biological healing, biomechanical properties, knee stability, and even a protective cartilage effect, as compared with a nonanatomic reconstruction [45][46][47][48][49].…”
Section: Mechanical Stimulimentioning
confidence: 99%
“…These authors suggest that achieving anatomical graft placement on the femur is crucial to restoring normal knee function and may theoretically decrease the rate of joint degeneration after ACL reconstruction. Okafor et al (2014) showed that patients with nonanatomical ACL reconstruction demonstrated a significant decrease in cartilage thickness along the medial intercondylar notch in the operative knee relative to the intact knee. In the anatomic group, no significant changes were observed.…”
Section: Introductionmentioning
confidence: 99%